Urgent surgery after emergency presentation for colorectal cancer has no impact on overall and disease-free survival: a propensity score analysis. Issue 1 (December 2016) - Weixler, Benjamin; Warschkow, Rene; Ramser, Michaela; Droeser, Raoul; von Holzen, Urs; Oertli, Daniel; Kettelhack, Christoph
Abstract Background It remains a matter of debate whether colorectal cancer resection in an emergency setting negatively impacts on survival. Our objective was therefore to assess the impact of urgent versus elective operation on overall and disease-free survival in patients undergoing resection for colorectal cancer by using propensity score adjusted analysis. Methods In a single-center study patients operated for colorectal cancer between 1989 and 2013 were identified from a prospectively maintained database. Median follow-up was 44 months. Patients with neoadjuvant treatment were excluded. The impact of urgent operation on overall and disease-free survival was assessed using both Cox regression and propensity score analyses. Results Of 747 patients with colorectal cancer, 84 (11 %) had urgent and 663 elective cancer resection. The propensity score revealed strongly biased patient characteristics (0.22 ± 0.16 vs. 0.10 ± 0.09;P < 0.001). In unadjusted analysis urgent operation was associated with a 35 % increased risk of overall mortality (hazard ratio(HR) of death = 1.35, 95 % confidence interval(CI):1.02–1.78, P = 0.045). In risk-adjusted Cox regression analysis urgent operation was not associated with poor overall (HR = 1.08, 95 %CI:0.79–1.48;P = 0.629) or disease-free survival (HR = 1.02, 95 %CI:0.76–1.38;P = 0.877). Similarly in propensity score analysis urgent operation did not influence overall (HR = 0.98, 95 % CI:0.74–1.29), P = 0.872) and disease-free survival (HR = 0.89, 95 %CI:0.68 to 1.16, P = 0.387). Conclusions This study provides evidence that worse oncologic outcomes after urgent operation for colorectal cancer are caused by clinical circumstances and not due to the urgent operation itself. Urgent operation is not a risk factor for colorectal cancer resection.